2021
DOI: 10.3389/fnmol.2021.718387
|View full text |Cite
|
Sign up to set email alerts
|

Period 2: A Regulator of Multiple Tissue-Specific Circadian Functions

Abstract: The zebrafish represents a powerful model for exploring how light regulates the circadian clock due to the direct light sensitivity of its peripheral clocks, a property that is retained even in organ cultures as well as zebrafish-derived cell lines. Light-inducible expression of the per2 clock gene has been predicted to play a vital function in relaying light information to the core circadian clock mechanism in many organisms, including zebrafish. To directly test the contribution of per2 to circadian clock fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A loss of dec1 using morpholino antisense technology suggests a role for this gene in controlling circadian rhythms of locomotor activity induced by a light pulse but a role for this gene in period control in LL has not been addressed (Ben-Moshe et al, 2014). Along the same line a double mutant line for per2 and cry1a exhibit deficits in the generation of rhythms following a light pulse but the role of cry1a during period control in LL has not been addressed (Hirayama et al, 2019) In contrast, per2 regulates period length in constant light but its transcription is not affected in opn4xa -/- larvae ((Ruggiero et al, 2021; Wang et al, 2015); Figure 5G)); it is however possible that affecting the level of CRY1A could modify PER2 activity therefore leading to the observed phenotype. Further experiments will be required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of dec1 using morpholino antisense technology suggests a role for this gene in controlling circadian rhythms of locomotor activity induced by a light pulse but a role for this gene in period control in LL has not been addressed (Ben-Moshe et al, 2014). Along the same line a double mutant line for per2 and cry1a exhibit deficits in the generation of rhythms following a light pulse but the role of cry1a during period control in LL has not been addressed (Hirayama et al, 2019) In contrast, per2 regulates period length in constant light but its transcription is not affected in opn4xa -/- larvae ((Ruggiero et al, 2021; Wang et al, 2015); Figure 5G)); it is however possible that affecting the level of CRY1A could modify PER2 activity therefore leading to the observed phenotype. Further experiments will be required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Following two‐way ANOVA, differences for heterozygote ( bsx +/ − ) and mutant ( bsx −/− ) fish compared to those of wildtype ( bsx +/+ ) controls were determined by multiplicity‐adjusted Dunnett's multiple comparisons tests. For the analysis of rhythmic locomotor activity, the data were normalized, and the period, phase, and amplitude were calculated as recently described 31 . Statistical differences in period and amplitude between groups were determined by ANOVA (followed by Tukey's multiple comparisons tests), and statistical differences in phase were determined by Watson–Williams test for the homogeneity of means by use of R software.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of rhythmic locomotor activity, the data were normalized, and the period, phase, and amplitude were calculated as recently described. 31 Statistical differences in period and amplitude between groups were determined by ANOVA (followed by Tukey's multiple comparisons tests), and statistical differences in phase were determined by Watson–Williams test for the homogeneity of means by use of R software. Values are presented as mean with standard error (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were entrained for 4 days on a 12 : 12 LD cycle prior to the experiment, and ZT21 was chosen as the time of the light pulse, as previous phase response curve data in zebrafish has shown that this is the time of day that the zebrafish cells are robustly light responsive [35]. The light-responsive clock genes cry1a and per2a, as well as the light-sensitive DNA repair gene cyclobutane pyrimidine dimer photolyase (CPD-Ph), were selected as marker genes for light sensitivity, as these genes appear to be activated using different pathways [36][37][38][39].…”
Section: (A) Induction Of Clock Genes Depends On Duration and Intensi...mentioning
confidence: 99%